(untitled) (Journal of Civil Engineering Researchers, 2020)
This paper first offers information on blast wave and blast loading. Then, the dynamic analysis of a single concrete slab against blast loading was conducted by the ABAQUS software program. Maximum stress in CFRP plates in the center of the reinforced concrete slab was observed in all loading phases, since this area was in the maximum stress zone. It is also an efficient method of retrofitting the slabs against blast loading using externally fiberreinforced polymer attached to the tensile side of the slab. © 2017 Journals-Researchers.